PENGBlock pra Epidural Anestesia - Edlin -; Mual Kristian Sinaga (Universitas Prima Indonesia, 2022)
Backgrounds: Patients with hip fractures are common in geriatric patients. Severe pain often found in cases hip fracture, especially in sitting and tilt position. This complicate anesthetic procedures, especially in regional anesthesia such as epidural or spinal, and patient must positioned on side sitting position. Objective: implementing PENG block is to block nerve fibers in the articular branch supplied by femoralis, obturator and obturator accessory nerves area. PENG blocks performed postoperative pain relief for hip joint surgery or management posttraumatic pain associated proximal femoral/femoral head fractures which patients is unable to withstand pain when positioned sitting or tilted, it is often necessary to add general anesthetic to reduce pain. With the reason of avoiding general anesthesia, PENG block temporarily relieves pain, so patients could be positioned freely sitting or tilt. Case: This case report describes a 79-year-old woman with pelvic pain due to a fall. The patient only can lie down and cannot change position. Patient has history of hypertension, cardiac catheterization surgery and stroke. Discussion: patient given PENG block to minimize pain and positioned to a sitting position. Anesthesia followed by epidural anesthesia. Operation lasts approximately 5 hours. There were no complaints of pain during and after surgery. Mobilization can be done within 6 hours after surgery. Conclusion: The PENG block technique used in this case is able to minimize pain so that the patient can be positioned freely and allows regional anesthesia to be performed.